Analysis from a personalist bioethics perspective on the role of the hospital pharmacist in euthanasia - Mateo-Folgado, Esther (2025)
The word "euthanasia" comes from the Greek: "eu," meaning good, and "thanatos," meaning death; etymologically, it means "good death." However, in most legal texts, euthanasia is commonly defined as the medical act by which a person's death is caused directly and intentionally, with the person having voluntarily chosen it, due to a serious and incurable illness or a severe, chronic, and disabling condition. The regulation of euthanasia presents an ethical dilemma for the practice of healthcare professions, directly challenging their fundamental objective of caring for and safeguarding the lives of patients. The lack of training and information for hospital pharmacists in this area, as well as the progress made in developing responsible pharmaceutical care that is involved in the pharmacotherapy of patients, highlights the need for a thorough analysis of their roles and duties as healthcare professionals, as well as the implications of their involvement in euthanasia.